Analysis of Network Function Virtualization and Software Defined Virtualization - M. Sandeep Kumar; Prabhu j (Society of Visual Informatics, 2017)
Network function virtualization (NFV) has played important role in both industry and academic change in telecommunication services. NFV has the ability to handle reduction on OPEX and CAPEX; it provides new service and also increases quickly in getting a time value. NFV has an opportunity in doing research in developing new innovation in architecture, framework, and measures some of the technology used in deploying in NVF. In this paper, the author describes the relation between NFV, SDV and cloud computing. Â The architecture of NVF its advantage in using network function virtualization and some activity used in NFV and adoption of NVF and future direction of NFV, issues, and difference in NFV and SDV.